Asymmetric synthesis of functionalized chiral diphosphines via organopalladium promoted hydrophosphination and diels-alder reactions - Yuan, Mingjun (2011)
This thesis describes the asymmetric synthesis of functionalized chiral diphosphines via enantiomeric organopalladium complex (R-26) promoted asymmetric hydrophosphination and Diels-Alder reactions. Introduction of functionalities on chiral diphosphines using organic transformations with palladium template as protection is also demonstrated. In Chapter 1, a brief introduction on the synthesis and application of chiral diphosphines, research development in our research group and the aims of this project is presented. In Chapter 2, the ester- and keto-functionalized allylic monophosphine palladium complexes containing the ortho-metalated (R)-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary were synthesized via a versatile one-pot process. Subsequent asymmetric hydrophosphination of the coordinated allylic phosphine substrates generated the functionalized chiral 1,2-bis(diphenylphosphino)ethane products. The coordination properties and absolute configurations of the diphosphine ligands were established by single crystal X-ray crystallography. The optically pure 1,2-bis(diphenylphosphino)ethane ligands with ester and keto functionalities could be liberated in high yields from the corresponding dichloro palladium complexes by treatment with aqueous potassium cyanide.